ANALISIS PENGGUNAAN METODE TIKRAR PADA PEMBELAJARAN TATAP MUKA TERBATAS MENGHAFAL HADIS DI KELAS 5 SDIT SYAHIRAL ILMI BUKIT TINGGI - Ismira; Istiqomah As Sayfullooh; Jendriadi; Silfi Melindawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the use of the Tikrar as a method for memorizing hadith on limited face-to-face learning and its effect on students’ hadith memorization activities. Tikrar method refers to the memorizing method that emphasizes reading repetition so it can be a longterm memory for children. The research in this article was conducted by using a descriptivequalitative method. Data collection techniques included observation, interview, and documentation techniques with the researcher as the main instrument. The results showed that the implementation of the Tikrar method was applied by each student in the class by speaking out loud under the teacher’s guidance. At the end of the meeting, students were asked to reread the hadith that they had recited without reading the text. Based on the results of observation, interviews, and documentation, the tikrar method could make students easier to memorize hadith. The effectiveness of the Tikrar method in rote learning activities like memorizing the Al-Qur'an and memorizing hadith as the results of this research, produced conclusions and recommendations for the Islamic schools to use the Tikrar method in learning Al-Qur’an and Hadith.